A comparative study on the crisis communication approaches applied by Exxon Corporation in the Alaska oil spill and the Petron Corporation in the Guimaras oil spill - Amata, Dennis John M.; Evangelio, Alvin V. and Ramos, Revina M. 4 0 16; 5 (2010)
ABSTRACT The study determined the crisis communication approaches applied by Exxon Corporation in the Alaska, USA oil spill which happened on March 24, 1989, and Petron Corporation in Guimaras, Philippines oil spill which occurred on August 11, 2006. The two oil spill incidents are classic cases used in analyzing crisis management. The researchers explored the utilization of the crisis communication approaches by both companies during the pre-operational, operational and post operational period, through the use of conceptual literature such as books concerning public relations, case studies, news clippings, annual reports and journals. Also, the researchers capitalized the Internet for web posts regarding the study. These consolidated approaches were properly categorized and plotted in matrixes, using the set factors such as Media relations, Communication Management, Company Management Participation, Community Relations, Stakeholders Relations, Government and Regulatory Agency Relations and Employees' Involvement and Volunteering. The gathered primary data were analyzed through the interviews from significant resource persons (local and foreign PR practitioners, residents of affected communities, company representatives), related literatures, and public relations theories (Apologia Theory, Image Restoration Theory, Stakeholders Theory, Rectification and Remediation Crisis Strategies) This study maximized the potential of new media, as an effective tool in a research process since it provides the researchers a convenient network to reach out resource persons outside the country, and obtained important information. After analyzing the data, the researchers have found out that most of the communication approaches of Petron Corporation, were utilized very well, while Exxon Corporation exhibits poor utilization of their crisis communication approaches.
Undergraduate Thesis: (Bachelor in Mass Communication) - Pamantasan ng Lungsod ng Maynila 2010.
Keywords: 2 -- 0; 6; 20; 20; 2